Rhetoric and Rupture: A Theory of the Event - Mills, Robert (2011)
Rhetoric and Rupture: A Theory of the Event This thesis engages the problematic of agency and interiority in rhetorical studies by proposing a theory of evental rhetoric. The event is a rupture in the continuities of the symbolic, revealing the distance between the forces of symbolization and their phantasmagorical effects. This theory is built upon the works of Friedrich Nietzsche and Jacques Lacan, engaging questions of truth, being, and the relationship of the subject to herself and the world. The rhetorics of legal practice, particularly the per curiam opinions of the United States Supreme Court, I argue, provide the institutional and epistemological formations necessary to transcend the bonds of situated rhetoric and become truly evental. I turn to the Supreme Court decision in New York Times Co. v. United States as an example of such an evental rhetoric. These rhetorics clear the way for the introduction of the new, and found a conversation in which democracy can begin